2023
DOI: 10.3390/healthcare11081092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Demographic Distribution of Hypermobility in a Random Group of School-Aged Children in Nigeria

Abstract: Background: The purpose of this study was to determine the prevalence of hypermobility in randomly selected healthy children, without previous trauma or disease process affecting the joints and whether other demographic variables (age, sex, BMI) had an impact on Beighton scores and range of motion (RoM) in children between 6 and 10 years of age. Results: 286 children were included; 27.3% of them had a Beighton score ≥7/9 and 72% would be classified hypermobile if we had used a Beighton cut-off score ≥4/9. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…The prevalence of generalized joint hypermobility in the literature is 2-65%. This broad range may be due to different age groups and ethnicities of the included individuals, as well as various scoring systems and cut-off criteria [11,23,24]. The majority of these studies adopted the Beighton [21,25] or the Brighton criteria [26], with prevalence rates in university students ranging from 20% when the Brighton scale was utilized [27] to 26% with a cut-off Beighton score of ≥5 [27] and approximately 40% with a cut-off Beighton score of ≥4 [28].…”
Section: High Prevalence Of Hand Joint Hypermobility Among a Cohort O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of generalized joint hypermobility in the literature is 2-65%. This broad range may be due to different age groups and ethnicities of the included individuals, as well as various scoring systems and cut-off criteria [11,23,24]. The majority of these studies adopted the Beighton [21,25] or the Brighton criteria [26], with prevalence rates in university students ranging from 20% when the Brighton scale was utilized [27] to 26% with a cut-off Beighton score of ≥5 [27] and approximately 40% with a cut-off Beighton score of ≥4 [28].…”
Section: High Prevalence Of Hand Joint Hypermobility Among a Cohort O...mentioning
confidence: 99%
“…Studies conducted on medical, physical therapy, and music students revealed a prevalence of generalized joint hypermobility of approximately 13-27% [4,8,9], often accompanied by musculoskeletal complaints and psychological distress [4,10]. While several studies have investigated the prevalence of generalized joint hypermobility, specific estimates for the prevalence of localized and peripheral joint hypermobility are limited [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have explored the relationship between kinaesthesia, physical fitness, motor performance and joint hypermobility have shown inconsistent results [ 12 16 ]. Studies seeking to explore correlations between joint hypermobility and health outcomes in an African context are scarce despite the high prevalence of GJH recorded in Africa [ 17 , 18 ]. It is important to explore and identify how joint mobility modulate the clinical outcomes of children in an African setting.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that children in Africa have different living and activity patterns compared to Western children, they may not present complaint yet, but that does not rule out the risk of developing complaints as they age. Given the high prevalence of GJH in Nigeria [ 17 , 18 ], it was important to conduct this study within the Nigerian context. This study therefore explores the relationship between kinaesthesia, motor performance, physical fitness and joint mobility in children, which may provide directions for future longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%